Le potentiel de l'objet dans le discours - Boily, Lise (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1982)
AbstractDiscourse analysis provides a model for an approach in material culture. There is a complementarity between the potential of the discourse and the potential of the object. It is possibletoidentify paradigms in thesame syntagmatic chain that works simultaneously in the material order as well as in the spiritual one.